The Impact of the CSRD and the ESRS on Non-Financial Disclosure - Tommaso Fornasari; Marco Traversi (Symphonya, 2024)
The paper examines the evolution of non-financial reporting in Europe, propelled by significant regulatory changes including the Corporate Sustainability Reporting Directive (CSRD) and the European Sustainability Reporting Standards (ESRS) adoption. With the European Green Deal as a backdrop, we explore how sustainability has transitioned from a compliance obligation to a strategic imperative fundamentally reshaping corporate behaviour. By integrating Environmental, Social, and Governance (ESG) factors into corporate strategies, the new framework enhances transparency, fosters stakeholder trust, and prepares companies for the challenges and opportunities of sustainable operation. We discuss the potential of the European model to set global reporting standards and outline future research directions to assess the effectiveness of standards and their impact on corporate performance, investor behavior, and consumer trust.